Electronic government concepts, methodologies, tools and applications - Anttiroiko, Ari-Veikko. (IGI Global (701 E. Chocolate Avenue, Hershey, Pennsylvania, 17033, USA), 2008)
"This collection meets the need for quality, authoritative research in this domain with an authoritative collection. Studies from the electronic government researchers worldwide enable libraries in academic, government, and other settings to provide a collection on topics like digital government, electronic justice, government-to-government, information policy, and cyber-infrastructure research and methodologies"--Provided by publisher.